Chemical composition and antimicrobial activity of essential oils from \(Angelica sinensis\) (Oliv.) diels cultivated in Hung Yen province of Vietnam - Ha, Chu Thi Thu; Huong, Nguyen Thi; Hanh, Nguyen Phuong; Hung, Nguyen Quang; Sinh, Nguyen Khang; Thuy, Dinh Thi Thu; Tuyen, Tran Thi; Ngoc, Nguyen Thi Hong; Tam, Nguyen Kieu Bang; Hang, Nguyen Thuy (Academia Journal of Biology, 2021)
Essential oils from roots, flowers, fruits, and leaves plus stems of Angelica sinensis cultivated in Vietnam were obtained by hydrodistillation and were analyzed using GC/MS-FID. In total, 36, 30, 33, and 27 compounds were found accounting for 98.7%, 98.8%, 99.2%, and 100% of the oils compositions, respectively. (Z)-Ligustilide (49.4%, 29.6%, 25.8%, 28.9%) and γ-terpinene (20.6%, 38.5%, 35.5%, 44.2%) were the main components of the respective essential oils. Especially, dictyopterene C (10.8%) was found to be one of the main components of fruit oil. Among the A. sinensis essential oil samples tested, the fruit oil revealed the strongest antimicrobial activity against bacteria Escherichia coli and yeast Candida albicans with median inhibitory concentration values of 0.97 and 0.15 mg/mL, respectively.